Optimization of the air-cooled supercapacitor module compartment for an electric bus. (5th February 2017) - Zhang, Xinglei; Wang, Wen; He, Haixia; Hua, Li; Heng, Jianpo
Highlights: Impact of external airflow on air distribution inside compartment is studied. Air cooling system of supercapacitor module compartment is optimized. Temperatures inside original and optimized module compartments are compared. Abstract: The air cooling system for the supercapacitor module compartment in an electric bus is optimized, where cooling air enters the supercapacitor module compartment from the passenger cabin, and then exits from air outlets located on the hull side of the bus. The air distribution inside compartment is affected by external airflow through the outlets of the compartment during bus running on the road. Moreover, the external airflow prevents the cooling air from flowing out. In consideration of the effect of external airflow on the air distribution inside compartment, the air cooling system is optimized by adjusting the structure and location of compartment outlets. Experimental temperatures verify that the optimized air cooling system can satisfy thermal management of supercapacitor modules in electric bus.